Adsorption and corrosion inhibition behavior of hydroxyethyl cellulose and synergistic surfactants additives for carbon steel in 1 M HCl. (20th January 2017) - Mobin, Mohammad; Rizvi, Marziya
Highlights: HEC was investigated as efficient corrosion inhibitor for mild steel in 1 M HCl. Synergistic effect of surfactants on inhibition behavior of HEC was also investigated. Methods used for investigation are Gravimetric, electrochemical, AFM and SEM-EDX. Quantum chemical and UV–vis analysis furthur explain the adsorption process of HEC. HEC acts as a mixed-type inhibitor. Abstract: The inhibitory effect of hydroxyethylcellulose (HEC) on A1020 carbon steel corrosion in 1 M HCl solution was evaluated at different concentrations and temperatures using weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), UV–vis spectrophotometry, scanning electron microscopy (SEM), energy dispersive x-ray analysis (EDX), atomic force microscopy (AFM) and quantum chemical analysis. Inhibition efficiency was found to increase with increase in concentration of HEC but decreased with increasing temperature. Inhibitory effect of HEC mixed with minimal concentration of surfactants, triton X 100 (TX), cetyl pyridinium chloride (CPC) and sodium dodecyl sulfate (SDS) was also evaluated. HEC gets adsorbed onto the mild steel surface via mixed type adsorption. Ea, ΔH, ΔS and ΔG⁰ads, the thermodynamic and activation parameters, were calculated and discussed. Adsorption of inhibitor on the steel/solution interface follows Langmuir adsorption isotherm. EIS suggests formation of protective layer over the carbon steel surface. Results of different experimental techniques pertaining to the inhibitory effect of HEC and HEC mixed with surfactants are in good agreement with theoretical quantum chemical investigation.